PROFIL PASIEN KANKER OVARIUM DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR – BALI PERIODE JULI 2013 – JUNI 2014 - Ida Ayu Dhitayoni; I Nyoman Gede Budiana (Universitas Udayana, 2017)
Ovarian cancer is the most deadly gynecological cancer with the lowest five year survival rate among other gynecological cancers in the world, it happens because early diagnosis for ovarian cancer is arduous. Nowadays, early diagnosis depends largely on knowledge about the profile of the patient in a region. This research carried out to know ovarian cancer patients’ characteristic in RSUP Sanglah in the period of July 2013 until June 2014. In this research, medical record of patients who came in this period acquired from medical record installation are used to obtain data. Next, data is processed and served in descriptive manner as mean, median, and average. From this research, there are 73 (15.33%) ovarian cancer patients from 476 cases of gynecological cancers in RSUP Sanglah in this research period. Most of patients are 41 – 50 years old (38.4%), 50.7% diagnosed in IIIC stage, 87.67% with epithelial type, 24.66% with serous subtype and 79% has parity ? two. The mean for body mass index is 22.77 kg/m2.As much as 17.8% patient used hormonal contraception. Thus, this research obtained ovarian cancer has the second highest prevalence of gynecological cancers in RSUP Sanglah after cervical cancer, with patient profile as follow: prominent in 4th to 5th decade of life, mostly diagnosed in stage IIIC, has serous epithelial subtype, parity ? two, and normal body mass index. The use of hormonal contraceptives in patients is low.